2011 Seventh International Conference on Mobile Ad-Hoc and Sensor Networks 2011
DOI: 10.1109/msn.2011.25
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Scheduling in Highly Dynamic Environments Using Error Inference

Abstract: Abstract-Energy constraint is a critical hurdle hindering the practical deployment of long-term wireless sensor network applications. Turning off (i.e., duty cycling) sensors could reduce energy consumption, however at the cost of low sensing fidelity due to sensing gaps introduced. Existing techniques have studied how to collaboratively reduce the sensing gap in space and time, however none of them provides a rigorous approach to confine sensing error within desirable bounds. In this work, we propose a collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Sink or CHs performs reclustering in case of centralized schemes. In [10] scheduling mechanism for collaborating sensors and attain error-bound scheduling control to monitor applications is utilized and the advantages of both methods to strike a compromise between energy consumed and prediction accuracy. Sensing planned based on two error information, a) error calculated locally b) error predicted by neighboring nodes.…”
Section: Related Workmentioning
confidence: 99%
“…Sink or CHs performs reclustering in case of centralized schemes. In [10] scheduling mechanism for collaborating sensors and attain error-bound scheduling control to monitor applications is utilized and the advantages of both methods to strike a compromise between energy consumed and prediction accuracy. Sensing planned based on two error information, a) error calculated locally b) error predicted by neighboring nodes.…”
Section: Related Workmentioning
confidence: 99%
“…We developed a prototype system by adding a combination of internal group and inter-group data reduction while trying to maintain data integrity at an acceptable level. Our previous work [10] has shown that a statistical approach can help to predict the future sensing data under predefined tolerance. However using machine learning approach in data reduction is new as the data processing center can predict the data both inside group and inter-group with sending request which normally consume large amount of energy in packets dissemination.…”
Section: A Data Management In Dr3mentioning
confidence: 99%
“…The collaborative scheduling was studied in [24]. The authors provided a collaborative scheme based on the concept of error interference.…”
Section: Collaborative Schedulingmentioning
confidence: 99%